We Are an Open-Door School: Institutional Factors Facilitating the Concentration of Migrant Students in Schools in Santiago, Chile - Cordoba-Calquin, C (ARIZONA STATE UNIV, MARY LOU FULTON TEACHERS COLL, 2025)
Currently, 8% of the total number of students enrolled in Chile have a foreign origin. Most of them attend public schools and are concentrated in a few schools. Therefore, there is a tendency towards segregation of these students, as in other countries. This study provides elements for the analysis of the institutional aspects that influence this phenomenon. A case study was carried out with three public elementary schools located in the city of Santiago that in 2018 had a high proportion of migrant students. A mixed methodology is used, including the analysis of data on the evolution of enrolment and interviews with directors. These schools occupied a middle or low position in the scholar market and had been experiencing a loss of Chilean students, which led them to be open to enrolling migrant students. This allowed them to stabilize their enrollment, while attracting this type of population. The process is not free of tensions, one of the most relevant being they do not receive the resources associated with the Law of School Preferential Subsidy (SEP; Subvenci & oacute;n Escolar Preferencial, in Spanish), given the situation of administrative irregularity in which many of students families find themselves.